Light conversion coated glass
By applying composite light conversion coating technology on photovoltaic glass, the combination of rare earth doped materials and nanomaterials can absorb and convert ultraviolet and infrared light into visible light, which solves the problem of low utilization rate of photovoltaic cells for wide spectrum light, and significantly improves the photoelectric conversion efficiency of photovoltaic cells.
Patent Information
- Application Number
- CN202411678484.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
AI Technical Summary
The utilization rate of existing photovoltaic cell materials for ultraviolet and infrared light is low, which limits the photoelectric conversion efficiency and application fields of photovoltaic cells.
Using composite light conversion coating glass, including transparent conductive glass layer, downconversion coating and upconversion coating, absorbs ultraviolet and infrared light and converts it into visible light through a combination of rare earth doped materials and nanomaterials.
The utilization rate of ultraviolet and infrared light has been improved, the photoelectric conversion efficiency of photovoltaic cells has been improved, and the specific increase is 5 to 8%.
Smart Images

Figure HDA0005147670610000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic glass, and in particular to a light-conversion coated glass. Background Art
[0002] With the continuous increase in global energy demand and the enhancement of environmental protection awareness, photovoltaic technology has been widely used as a clean and renewable energy form. However, the efficiency of current photovoltaic cells is limited by the incident spectrum, especially the low utilization of ultraviolet (UV) and infrared (IR). Traditional photovoltaic cell materials have high absorption efficiency for visible light, but the conversion efficiency is low for shorter wavelength ultraviolet light and longer wavelength infrared light. This not only limits the photoelectric conversion efficiency of photovoltaic cells, but also restricts its application in a wider range of fields.
[0003] In order to solve this problem, researchers have explored a variety of methods in recent years to improve the utilization efficiency of photovoltaic cells for wide-spectrum light. Among them, the introduction of photoconversion materials is an effective solution. By applying a photoconversion coating on the surface of photovoltaic cells, ultraviolet light and infrared light that cannot be directly absorbed by photovoltaic materials can be converted into visible light, thereby enhancing the light absorption capacity of photovoltaic cells and improving the photoelectric conversion efficiency of the cells. At present, photoconversion materials are mainly divided into down-conversion materials and up-conversion materials. Down-conversion materials absorb high-energy ultraviolet light and re-emit visible light wavelengths; up-conversion materials convert infrared light into higher-energy visible light. Although this method can effectively improve the photoelectric conversion efficiency of photovoltaic cells in theory, how to improve the conversion efficiency of up- and down-conversion coatings, and how to achieve uniform and stable coating on photovoltaic glass are still technical difficulties.
[0004] With the rapid development of photovoltaic technology, there are already a variety of light conversion technologies on the market for improving the photoelectric conversion efficiency of photovoltaic cells. Existing photovoltaic glass mainly uses coating or material modification to increase the absorption rate of the solar spectrum. However, these technologies usually focus on improving the responsiveness of photovoltaic cells to visible light, ignoring the use of ultraviolet light (UV) and infrared light (IR). Ultraviolet light and infrared light account for 6%-7% and about 53% of the solar spectrum respectively. If they can be effectively used, the power generation efficiency of photovoltaic cells will be significantly improved.
[0005] Currently, most of the existing light conversion coatings on the market use a single down-conversion or up-conversion technology, which makes it difficult to take into account the dual conversion of ultraviolet light and infrared light. For example, some coating materials use rare earth elements (such as lanthanides) to absorb ultraviolet light and emit it as visible light, but the use of infrared light is relatively limited. Infrared conversion materials are relatively rare, and usually have problems such as low emission efficiency and high energy loss. In addition, most of the light conversion coatings in the existing market are single-layer structures, resulting in low conversion efficiency, and the stability and weather resistance of the coating materials also limit their wide application. Summary of the invention
[0006] In order to overcome the above-mentioned defects of the prior art, the present invention provides a light conversion coated glass to improve the photoelectric conversion efficiency of photovoltaic cells.
[0007] In order to achieve the above-mentioned purpose of the invention, the present invention provides a light-conversion coated glass, wherein the coated glass comprises a transparent conductive glass layer, an up-conversion coating for absorbing infrared light and emitting visible light, a down-conversion coating for absorbing ultraviolet light and emitting visible light, a nickel oxide hole transport layer, a perovskite light absorption layer, a C60 layer, an electron transport layer and a Cu layer, wherein the transparent conductive glass layer, the down-conversion coating, the up-conversion coating, the nickel oxide hole transport layer, the perovskite light absorption layer, the C60 layer, the electron transport layer and the Cu layer are arranged in sequence from bottom to top.
[0008] Furthermore, the preparation method of the down-conversion coating comprises:
[0009] Raw material preparation:
[0010] Rare earth dopant: rare earth element yttrium oxide and europium-doped yttrium oxide are selected as doping materials for the down-conversion coating to absorb ultraviolet light and convert it into visible light, wherein the doping concentration is 2 to 5 mol% to obtain high conversion efficiency and stable light emission performance;
[0011] Other reagents: Deionized water and anhydrous ethanol were used as the main solvents in the dissolution process; ammonia was used as a precipitant to promote the precipitation of hydroxides of rare earth elements;
[0012] Down conversion coating solution:
[0013] Dissolve yttrium nitrate and europium nitrate in 250 mL of deionized water, and control the europium content in the range of 2 to 5 mol% to ensure the conversion efficiency of the down-conversion coating; stir the above solution evenly, add an appropriate amount of ammonia water with a concentration of 0.1 mol / L, and gradually adjust the pH value to 8 to 10 to form a precipitate of yttrium hydroxide and europium hydroxide; after the precipitate is formed, remove the liquid by vacuum filtration, and wash the precipitate with deionized water for multiple times until the pH is 6.8 to 7.2;
[0014] Down conversion coating deposition:
[0015] The hydroxide precipitate of the down-conversion material is dried in an oven at 80°C for more than 3 hours to remove moisture; the precipitate of the down-conversion material after drying is calcined at a high temperature of 1000°C for more than 2 hours to obtain a stable europium-doped yttrium oxide powder; the prepared europium-doped yttrium oxide powder is dissolved in anhydrous ethanol and evenly dispersed with a stirrer; the solution is evenly coated on the cleaned transparent conductive glass layer by spin coating technology to form a down-conversion coating with a thickness of 100 to 200 nanometers.
[0016] Furthermore, after the deposition of the down-conversion coating is completed, the down-conversion coating is dried at 60° C. and low-temperature annealed at 150° C. for 30 minutes to increase the interlayer bonding strength and improve the weather resistance and structural stability of the coating.
[0017] Furthermore, the preparation method of the up-conversion coating comprises:
[0018] Raw material preparation:
[0019] Up-conversion coating nanoparticles: Nanomaterials containing erbium, yttrium and gadolinium are used as doping materials for up-conversion coatings. These materials can absorb infrared light and convert it into visible light. The erbium content is 0.5-1 mol% to achieve the best infrared light conversion effect.
[0020] Other reagents: Deionized water and anhydrous ethanol were used as the main solvents in the dissolution process; ammonia was used as a precipitant to promote the precipitation of hydroxides of rare earth elements;
[0021] Upconversion coating solution:
[0022] An upconversion coating solution is prepared in 200 mL of anhydrous ethanol, using a rare earth compound containing erbium with a mass concentration of 0.5 to 1 mol %; rare earth powder is ultrasonically dispersed in anhydrous ethanol for more than 1 hour to obtain a uniform solution, and the solution is added to the glass surface and evenly distributed;
[0023] Upconversion coating deposition:
[0024] The up-conversion nanomaterial is uniformly dispersed in an ethanol solution and stirred under ultrasonic conditions for more than 1 hour; the up-conversion material is coated on the down-conversion coating by spraying or spin coating; the deposition thickness is 50 to 100 nanometers to ensure the optical transparency of the coating and avoid excessive infrared light reflection.
[0025] Furthermore, after the up-conversion coating is deposited, it is dried at 60° C. and annealed at 150° C. for 30 minutes to increase the interlayer bonding strength and improve the weather resistance and structural stability of the coating.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] Light conversion coated glass can effectively convert ultraviolet light and infrared light into visible light, improve the utilization rate of incident light, and thus improve the photoelectric conversion efficiency of photovoltaic cells;
[0028] By setting a down-conversion coating, the utilization rate of ultraviolet light can be increased by 10-15%, and the incident amount of visible light can be increased, thereby improving the overall photoelectric conversion efficiency of the light-conversion coated glass by 2-3%;
[0029] By setting up the up-conversion coating, the utilization rate of infrared light can be increased by 8-12%, the incident amount of visible light can be further increased, and the overall photoelectric conversion efficiency of the light conversion coated glass can be increased by 3-5%;
[0030] After the down-conversion coating and the up-conversion coating are compounded, the down-conversion and up-conversion technologies are comprehensively utilized, and the overall photoelectric conversion efficiency of the light-conversion coated glass can be increased by 5 to 8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the cross-sectional structure of the coated conversion glass according to an embodiment of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the invention, rather than all the embodiments. The embodiments of the present invention are described below in conjunction with the drawings.
[0033] The light conversion coated glass of the present application converts ultraviolet light (UV) and infrared light (IR) into visible light by applying light conversion coating technology on the surface of photovoltaic glass, thereby improving the photoelectric conversion efficiency of photovoltaic cells; this is specifically achieved by compounding the down-conversion coating 2 and the up-conversion coating 3;
[0034] Down-conversion coating 2: A down-conversion coating 2 containing rare earth elements, such as europium-doped yttrium oxide (Eu), is deposited on the surface of the transparent conductive glass layer 1. These coatings can absorb high-energy ultraviolet light and re-emit it as lower-energy visible light, thereby improving the photoelectric conversion efficiency of the photovoltaic cell by converting ultraviolet light into visible light;
[0035] Up-conversion coating 3: a coating of nanomaterials containing erbium, yttrium and gadolinium is deposited on the down-conversion coating 2. These nanomaterial particles can absorb low-energy infrared light and re-emit it as high-energy visible light, thereby improving the photoelectric conversion efficiency of the photovoltaic cell by converting infrared light into visible light;
[0036] Multilayer composite structure: composite the down-conversion coating 2 and the up-conversion coating 3, optimize the coating thickness and material dosage after composite, and maximize the conversion efficiency of ultraviolet light and infrared light;
[0037] refer to Figure 1A light conversion coated glass comprises a transparent conductive glass layer 1, an up-conversion coating 3 for absorbing infrared light and emitting visible light, a down-conversion coating 2 for absorbing ultraviolet light and emitting visible light, a nickel oxide hole transport layer 4, a perovskite light absorption layer 5, a C60 layer 6, an electron transport layer 7 and a Cu layer 8, wherein the transparent conductive glass layer 1, the down-conversion coating 2, the up-conversion coating 3, the nickel oxide hole transport layer 4, the perovskite light absorption layer 5, the C60 layer 6, the electron transport layer 7 and the Cu layer 8 are sequentially arranged from bottom to top, the down-conversion coating 2 is arranged on the transparent conductive glass layer 1, and the up-conversion coating 3 is arranged on the down-conversion coating 2;
[0038] The preparation method of the down-conversion coating 2 comprises:
[0039] Raw material preparation:
[0040] Rare earth dopant: rare earth element yttrium oxide (Y3O3) and europium-doped yttrium oxide (Eu2O3) are selected as doping materials for the down-conversion coating 2 to absorb ultraviolet light and convert it into visible light, wherein the doping concentration is 2 mol% or 5 mol%. In other implementations of this embodiment, the doping concentration of the rare earth dopant is 3.5 mol%. It is found through experiments that when the doping concentration is 2 mol% to 5 mol%, high conversion efficiency and stable light emission performance can be obtained;
[0041] Other reagents: Deionized water and anhydrous ethanol are used as the main solvents in the process of dissolving the rare earth dopant; ammonia is used as a precipitant to promote the precipitation of the hydroxide of the rare earth element;
[0042] Solution for lower conversion coating 2:
[0043] Dissolve yttrium nitrate (Y(NO3)3) and europium nitrate (Eu(NO3)3) in 250 mL of deionized water, control the europium content to 2-5 mol%, in other embodiments of the present embodiment, the europium content is 2 mol% or 5 mol%, to ensure the conversion efficiency of the lower conversion coating 2; stir the above solution evenly, add an appropriate amount of ammonia water with a concentration of 0.1 mol / L, and gradually adjust the pH value to 8-10 to form a precipitate of yttrium hydroxide and europium hydroxide. In other embodiments of the present embodiment, the pH value is adjusted to 8.5-9.5; after the precipitate is formed, remove the liquid by vacuum filtration, and wash the precipitate with deionized water for several times until the pH is 6.8-7.2, remove the liquid by vacuum filtration, and wash the precipitate with deionized water for several times until the pH is 6.9-7.1;
[0044] Lower conversion coating 2 deposition:
[0045] The hydroxide precipitate of the down-conversion material is dried in an oven at 80° C. for more than 3 hours to remove moisture; the precipitate of the down-conversion material after drying is calcined at a high temperature of 1000° C. for more than 2 hours to obtain a stable europium-doped yttrium oxide powder; the prepared europium-doped yttrium oxide powder is dissolved in anhydrous ethanol and evenly dispersed with a stirrer; the solution is evenly coated on the cleaned transparent conductive glass layer 1 by spin coating technology to form a down-conversion coating 2 with a thickness of 100 to 200 nanometers. In other implementations of this embodiment, the down-conversion coating 2 can be 100 nanometers or 200 nanometers, or can be set to a thickness of 150 nanometers. The specific thickness can be set according to the light conversion efficiency;
[0046] After the deposition of the lower conversion coating 2 is completed, the lower conversion coating 2 is dried at 60° C. and low-temperature annealed at 150° C. for 30 minutes to increase the interlayer bonding force and improve the weather resistance and structural stability of the coating.
[0047] The preparation method of the up-conversion coating 3 comprises:
[0048] Raw material preparation:
[0049] Nanoparticles of up-conversion coating 3: Nanomaterials containing erbium (Er), yttrium (Y) and gadolinium (Gd) elements are used as doping materials of up-conversion coating 3. These materials can absorb infrared light and convert it into visible light. The content of erbium is 0.5-1 mol%. In other implementations of this embodiment, the content of erbium is 0.5 mol% or 1 mol%, or 0.8 mol%, to achieve the best infrared light conversion effect;
[0050] Other reagents: Deionized water and anhydrous ethanol were used as the main solvents in the dissolution process; ammonia was used as a precipitant to promote the precipitation of hydroxides of rare earth elements;
[0051] Solution for upconversion coating 3:
[0052] An upconversion coating 3 solution is prepared in 200 mL of anhydrous ethanol, using an erbium-containing rare earth compound with a mass concentration of 0.5 to 1 mol%. In other implementations of this embodiment, the mass concentration of the erbium rare earth compound is 0.5 mol% or 1 mol%. Rare earth powder is ultrasonically dispersed in anhydrous ethanol for more than 1 hour to obtain a uniform solution, and the solution is added to the glass surface and evenly distributed;
[0053] Upconversion coating 3 deposition:
[0054] The up-conversion nanomaterial is uniformly dispersed in an ethanol solution and stirred under ultrasonic conditions for more than 1 hour; the up-conversion material is coated on the down-conversion coating 2 by spraying or spin coating; the deposition thickness is 50 to 100 nanometers. In other implementations of this embodiment, the deposition thickness of the up-conversion coating 3 is 50 nanometers or 100 nanometers, or 75 nanometers, to ensure the optical transparency of the coating and avoid excessive infrared light reflection;
[0055] After the up-conversion coating 3 is deposited, it is dried at 60° C. and annealed at 150° C. for 30 minutes to increase the interlayer bonding strength and improve the weather resistance and structural stability of the coating.
[0056] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0057] Light conversion coated glass can effectively convert ultraviolet light and infrared light into visible light, improve the utilization rate of incident light, and thus improve the photoelectric conversion efficiency of photovoltaic cells;
[0058] By providing the down-conversion coating 2, the utilization rate of ultraviolet light can be increased by 10-15%, and the incident amount of visible light can be increased, thereby increasing the overall photoelectric conversion efficiency of the light-conversion coated glass by 2-3%;
[0059] By providing the up-conversion coating 3, the utilization rate of infrared light can be increased by 8-12%, the incident amount of visible light can be further increased, and the overall photoelectric conversion efficiency of the light conversion coated glass can be increased by 3-5%;
[0060] After the down-conversion coating 2 and the up-conversion coating 3 are combined, the overall photoelectric conversion efficiency of the light-conversion coated glass can be increased by 5 to 8% by comprehensively utilizing the down-conversion and up-conversion technologies.
[0061] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.
Claims
1. A light conversion coated glass, characterized in that: The coated glass includes a transparent conductive glass layer, an up-conversion coating for absorbing infrared light and emitting visible light, a down-conversion coating for absorbing ultraviolet light and emitting visible light, a nickel oxide hole transport layer, a perovskite light absorption layer, a C60 layer, an electron transport layer and a Cu layer. The transparent conductive glass layer, the down-conversion coating, the up-conversion coating, the nickel oxide hole transport layer, the perovskite light absorption layer, the C60 layer, the electron transport layer and the Cu layer are arranged in sequence from bottom to top.
2. The light conversion coated glass according to claim 1, characterized in that: The preparation method of the down-conversion coating comprises: Raw material preparation: Rare earth dopant: rare earth element yttrium oxide and europium-doped yttrium oxide are selected as doping materials for the down-conversion coating to absorb ultraviolet light and convert it into visible light, wherein the doping concentration is 2 to 5 mol% to obtain high conversion efficiency and stable light emission performance; Other reagents: Deionized water and anhydrous ethanol were used as the main solvents in the dissolution process; ammonia was used as a precipitant to promote the precipitation of hydroxides of rare earth elements; Down conversion coating solution: Dissolve yttrium nitrate and europium nitrate in 250 mL of deionized water, and control the europium content in the range of 2 to 5 mol% to ensure the conversion efficiency of the down-conversion coating; stir the above solution evenly, add an appropriate amount of ammonia water with a concentration of 0.1 mol / L, and gradually adjust the pH value to 8 to 10 to form a precipitate of yttrium hydroxide and europium hydroxide; after the precipitate is formed, remove the liquid by vacuum filtration, and wash the precipitate with deionized water for multiple times until the pH is 6.8 to 7.2; Down conversion coating deposition: The hydroxide precipitate of the down-conversion material is dried in an oven at 80°C for more than 3 hours to remove moisture; the precipitate of the down-conversion material after drying is calcined at a high temperature of 1000°C for more than 2 hours to obtain a stable europium-doped yttrium oxide powder; the prepared europium-doped yttrium oxide powder is dissolved in anhydrous ethanol and evenly dispersed with a stirrer; the solution is evenly coated on the cleaned transparent conductive glass layer by spin coating technology to form a down-conversion coating with a thickness of 100 to 200 nanometers.
3. The light conversion coated glass according to claim 2, characterized in that: After the deposition of the down-conversion coating is completed, the down-conversion coating is dried at 60° C. and low-temperature annealed at 150° C. for 30 minutes to increase the interlayer bonding force and improve the weather resistance and structural stability of the coating.
4. The light conversion coated glass according to claim 1, characterized in that: The preparation method of the up-conversion coating comprises: Raw material preparation: Up-conversion coating nanoparticles: Nanomaterials containing erbium, yttrium and gadolinium are used as doping materials for up-conversion coatings. These materials can absorb infrared light and convert it into visible light. The erbium content is 0.5-1 mol% to achieve the best infrared light conversion effect. Other reagents: Deionized water and anhydrous ethanol were used as the main solvents in the dissolution process; ammonia was used as a precipitant to promote the precipitation of hydroxides of rare earth elements; Upconversion coating solution: An upconversion coating solution is prepared in 200 mL of anhydrous ethanol, using a rare earth compound containing erbium with a mass concentration of 0.5 to 1 mol %; rare earth powder is ultrasonically dispersed in anhydrous ethanol for more than 1 hour to obtain a uniform solution, and the solution is added to the glass surface and evenly distributed; Upconversion coating deposition: The up-conversion nanomaterial is uniformly dispersed in an ethanol solution and stirred under ultrasonic conditions for more than 1 hour; the up-conversion material is coated on the down-conversion coating by spraying or spin coating; the deposition thickness is 50 to 100 nanometers to ensure the optical transparency of the coating and avoid excessive infrared light reflection.
5. The light conversion coated glass according to claim 4, characterized in that: After the up-conversion coating is deposited, it is dried at 60° C. and annealed at 150° C. for 30 minutes to increase the interlayer bonding strength and improve the weather resistance and structural stability of the coating.